Początki i rozwój kościelnego sądownictwa w Polsce na podstawie generalnego i okręgowych oficjalatów diecezji włocławskiej - Gręźlikowski, Janusz (Prawo Kanoniczne, 2001)
Ecclesiastical jurisdiction in Poland is a subject that has not been well studied. This article attempts to approach the beginnings and development of ecclesiastical jurisdiction in Poland by examples of the general and regional Włocławek Church official’s offices. At the beginning of the Church in Poland the bishops personally hed jurisdiction or they benefited from the help of priests that held a position closest to them that is archdeacons. The evolution of jurisdiction at the end of the XII century, as well as the insurance of an efficient court system in the Church, caused the Bishops to appoint steody judges. As even further impact on the development of jurisdiction in the Polish Church was caused by the IV constitution of Innocent Romana Ecclesia, from 1246, which specified the legal status and the competence of an official. The need for an efficient court system that in addition to the general official who hed his tribunal, the consistory, caused the bishops to also appointed Foral officials for a specified part of the dioecese and for certain categories of matters. These Foral officials had their own offices called Foral consistories or regional consistories. The largest diocese of Cracow and Gniezno had the most extent network of Church official’s offices. The diocese of Włocławek can be indudet as one of the leading diocese in the area of ecclesiastical jurisdiction. The general Church official’s office in Włocławek was established most probably as early as in the XIII century but archival records start in 1422. The Włocławek diocese, as the first in Poland, had a regional Pomeranian Church official’s office as early as 1289. Other dioceses established regional Church official’s offices as late as the end of the XIV century. The liquidation of regional Church official’s offices occurred in the beginning of the XIX century and from that time only general Church official’s offices functioned in the capitol of the diocese. This was a result of a reorganization of the administrative division of the Church in Poland that took place in 1925.